Pengaruh Manajemen Laba, Intellectual Capital dan Related Party Transaction terhadap Integritas Laporan Keuangan: Studi pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Salsabilla Hapiansyah, Natasya; Suryani, Elly; Luthfiyatul Farida, Ajeng (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In order for the information obtained by users of financial statements to be accounted for by the firm, financial statements and statements by corporations must be provided honestly, correctly, and without distortion or concealment. Users use financial reports as a decision-making tool since they provide an overview of the performance and growth of the organization. Conservativeness proxies may be used to evaluate the reliability of the financial accounts. To minimize fraud in financial reports and mistakes in decision-making, conservative accounting is the practice of presenting financial statements that are full of caution against important uncertainties and risks to a commercial business's situation. The goal of this research is to assess the financial reporting accuracy of manufacturing sector businesses listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021 in the areas of intellectual property, related party transactions, and earnings management. This study uses the manufacturing sector of the IDX as its sample population for the years 2018 through 2021. Purposive sampling was employed, and data was collected from 408 samples representing 102 different firms over the course of four years. Panel data regression analysis using the Eviews 10 software is used for this in-depth examination of the data, which involves several rounds of testing. Financial statement accuracy was shown to be impacted by the presence of related party transactions, intellectual property, and earnings management. Earnings management reduces financial statement reliability. On the other hand, related party transactions and intellectual property have no bearing on how accurate the financial records are.